2022
DOI: 10.3390/ijms23031784
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Cathepsin X in Glioblastoma: Interplay with γ-Enolase and the Effects of Selective Cathepsin X Inhibitors

Abstract: Glioblastoma (GBM) is the most common and deadly primary brain tumor in adults. Understanding GBM pathobiology and discovering novel therapeutic targets are critical to finding efficient treatments. Upregulation of the lysosomal cysteine carboxypeptidase cathepsin X has been linked to immune dysfunction and neurodegenerative diseases, but its role in cancer and particularly in GBM progression in patients is unknown. In this study, cathepsin X expression and activity were found to be upregulated in human GBM ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…On the other hand, the role of altered CTSZ proteolytic activity and cellular colocalization in poor prognosis in several human cancers has also been reported [68]. In gliomas, upregulation of CTSZ enzyme activity and colocalization with the total form of γ-enolase, especially in TAMs and microglia, suggest involvement in tumour progression and therapeutic targeting [69]. Altered expression and localization of CTSZ in hepatocytes are characteristic features of primary biliary cholangitis and other cholestatic liver diseases and are implicated in the progression of primary biliary cholangitis [70].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the role of altered CTSZ proteolytic activity and cellular colocalization in poor prognosis in several human cancers has also been reported [68]. In gliomas, upregulation of CTSZ enzyme activity and colocalization with the total form of γ-enolase, especially in TAMs and microglia, suggest involvement in tumour progression and therapeutic targeting [69]. Altered expression and localization of CTSZ in hepatocytes are characteristic features of primary biliary cholangitis and other cholestatic liver diseases and are implicated in the progression of primary biliary cholangitis [70].…”
Section: Discussionmentioning
confidence: 99%
“…In a fresh study that listed four subtypes of GBM, DAB2 is reported as one of the fifteen selected genes that belong to the classical (CL) subtype. S100A4 was found in the CL subtype of GBM [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proteolytic activity of cathepsin X results in C-terminal cleavage of γ-enolase, affecting its neurotrophic activity. The interplay between cathepsin X and γ-enolase was demonstrated by a correlation between the high proteolytic activity of cathepsin X and the C-terminal cleavage of γ-enolase [ 146 ].…”
Section: The Role Of γ-Enolase In Brain Cellsmentioning
confidence: 99%
“…Moreover, potent selective irreversible (AMS36) and reversible (Z7) inhibitors of cathepsin X decreased the viability of patient-derived glioblastoma multiforme cells in vitro as well as macrophages and microglia cultured in their conditioned media. Moreover, research has indicated that cathepsin X and γ-enolase are co-localized in glioblastoma multiforme tissues, especially in macrophages and microglia [ 146 ]. These findings suggest that cathepsin X plays a role in the progression of glioblastoma multiforme and is a potential target for therapeutic interventions against this aggressive brain tumor.…”
Section: The Role Of γ-Enolase In Brain Cellsmentioning
confidence: 99%